Application of Catalyst/UV/PU Nanocomposite for Removal of Tetracycline: Response Surface Methodology for Optimization and Kinetic Study - Mohammad Ansarizadeh; Tayebeh Tabatabaei; Mohammad Reza Samaei; Mostafa Leili; Mohammad Mehdi Baneshi (Shiraz University of Medical Sciences, 2021)
Background: Discharging antibiotics into the environment could cause great concern for scientists. In the present study, tetracycline (TC) antibiotic was photodegraded with titanium dioxide (TiO2) and zinc oxide (ZnO) fixed on the polyurethane (PU) in the presence of ultraviolet (UV) irradiation and optimized through response surface methodology (RSM). Methods: This experimental study was conducted on the most effective variables (pH, contact time, TC concentration, and catalyst doses) for experimental design. The experiments of degradation with the process of PU/UV/nanocatalyst composite were conducted with a reactor glass vessel (1000 mL) as batch mode. Results: The results showed that the quadratic model can be used for the interpretation of experiments. The results of the model represented that all parameters had a significant effect on the tetracycline removal, and the degradation of antibiotics was obtained at the optimum condition that was 95% for ZnO/UV/PU and 97% for TiO2/UV/PU. The main radical for the degradation of TC was hydroxyl ions based on the scavenger study and the first-order kinetic model was best fitted with data. The highest removal efficiency was obtained at pH of 5.2, catalyst dose of 2.64g/m2, TC concentration of 25.21, reaction time of 82 min using ZnO/UV/PU and pH of 5.8, catalyst dose of 2.9 g/m2, TC concentration of 25.12, and reaction time of 90 min using TiO2/UV/PU. Conclusion: It could be concluded that the process of nanocatalyst fixed on polyurethane can significantly eliminate the antibiotic in the presence of ultraviolet irradiation from the effluent of the wastewater treatment plant.